أثر النمو الإقتصادي على معدل البطالة في الأردن - دراسة قياسية تحليلية للفترة ( 1990 -2015 ) - ثامر علي, النويران; حمودي, حميدي بني خالد (Université de M'sila, 2017)
This study aims to measure the impact of economic growth on unemployment in Jordan during the period from 1991-2015, through analyzing the nature of that relationship. In order to achieve this goal, the study uses Time-Seriesin the study of the relationship between economic growth and unemployment through a combination of statistical methods.The study concludes that there was no impact of economic growth on unemployment in Jordan. In other words, the study defies the hypothesis: that economic growth has a positive and statistically sign ificantimpact on unemployment in Jordan.This result shows that a part of the unemployment in Jordan is not linked to the ability of the economy to create jobs (which can be called Structural Unemployment), in addition to the presence of foreign workers, which absorb a part of any impact of economic growth on unemployment whether negatively or positively
Keywords: البطالة ، النمو الإقتصادي ، الإقتصاد الأردني ( Unemployment, Economic Growth, Jordan Economy )